2016
DOI: 10.1002/2016gl067937
|View full text |Cite
|
Sign up to set email alerts
|

Synchronicity between ice retreat and phytoplankton bloom in circum‐Antarctic polynyas

Abstract: Phytoplankton in Antarctic coastal polynyas has a temporally short yet spatially variant growth window constrained by ice cover and day length. Using 18‐year satellite measurements (1997–2015) of sea ice and chlorophyll concentrations, we assessed the synchronicity between the spring phytoplankton bloom and light availability, taking into account the ice cover and the incident solar irradiance, for 50 circum‐Antarctic coastal polynyas. The synchronicity was strong (i.e., earlier ice‐adjusted light onset leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 34 publications
(53 reference statements)
3
22
0
Order By: Relevance
“…To restrict our interest to only Arctic sub-ice blooms, we excluded grid cells with less than 80% ice concentration, typically defined as the “marginal ice zone,” from the calculation (in contrast to J16, which included these regions when computing under ice primary production). As mentioned above, the marginal ice zone was previously considered the only site where sub-ice phytoplankton blooms were possible ( 38 , 39 ), but the focus of this study is on blooms underneath sea ice, where open-ocean or marginal ice zone processes, like wind-driven vertical mixing, are less important. We additionally exclude Baffin Bay from the study region to focus on the Arctic Basin alone.…”
Section: Resultsmentioning
confidence: 99%
“…To restrict our interest to only Arctic sub-ice blooms, we excluded grid cells with less than 80% ice concentration, typically defined as the “marginal ice zone,” from the calculation (in contrast to J16, which included these regions when computing under ice primary production). As mentioned above, the marginal ice zone was previously considered the only site where sub-ice phytoplankton blooms were possible ( 38 , 39 ), but the focus of this study is on blooms underneath sea ice, where open-ocean or marginal ice zone processes, like wind-driven vertical mixing, are less important. We additionally exclude Baffin Bay from the study region to focus on the Arctic Basin alone.…”
Section: Resultsmentioning
confidence: 99%
“…While it is difficult to measure the fine-scale location of a polynya at 25 km spatial resolution, the lower sea ice concentrations provide an indication of some open water near the coast, which for seabirds provides a source of open water for foraging. We have previously tested mapping polynyas using a SIC threshold of 0.75 and 0.85 for the NASA Team and Bootstrap algorithms, respectively, and found that these thresholds provided consistent polynya areas between the two algorithms and matched other estimates of the spatial distribution of polynyas (see Li et al, 2016). However, for this study we chose just one threshold, a compromise between the two algorithms, so that we can better determine the sensitivity of using the same threshold on polynya area and timing of formation.…”
Section: Methodsmentioning
confidence: 95%
“…Both polynyas and the MIZ are biologically important regions of the sea ice cover that have implications for the entire trophic web, from primary productivity (Yun et al, 2015) to top predator species, such as seabirds. Near the ice edge and in the MIZ, the stable upper layer of the water column is optimal for phytoplankton production (e.g., Park et al, 1999).…”
mentioning
confidence: 99%
“…Previous work has shown this metric to be highly correlated with phytoplankton‐bloom phenology, as deduced from ocean color, near Penguin breeding colonies (Li et al. ). We calculated bloom onset using a 250 km radius, which incorporates the size of most coastal polynyas (Arrigo and van Dijken , Arrigo et al.…”
Section: Methodsmentioning
confidence: 98%
“…This is calculated by taking the Julian day in which a particular light threshold is reached within a 250 km radius of the colony of interest, and applying a correction for light blocked by local sea ice (see Li et al. ). Previous work has shown this metric to be highly correlated with phytoplankton‐bloom phenology, as deduced from ocean color, near Penguin breeding colonies (Li et al.…”
Section: Methodsmentioning
confidence: 99%